2020
DOI: 10.1016/j.jocn.2020.04.003
|View full text |Cite
|
Sign up to set email alerts
|

EEG multifractal analysis correlates with cognitive testing scores and clinical staging in mild cognitive impairment

Abstract: Alzheimer's disease and mild cognitive impairment are increasingly prevalent global health concerns in aging industrialized societies. There are only limited non-invasive biomarkers for the cognitive and functional impairment associated with dementia. Multifractal analysis of EEG has recently been proposed as having the potential to be an improved method of quantitative EEG analysis compared to existing techniques (e.g., spectral analysis). We utilized an existing database of a study of healthy elderly patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…This network cooperates directly and uninterruptedly with the nervous system and exhibits similar cascade-like structure as found in "neuronal avalanches" [52]. It can be no small coincidence that tensegrity and avalanche models all converge on the same multifractal geometry [53,54] that inspired the development of multiscale PDF quantification of non-Gaussianity [22,24,55]. Hence, this bodywide aspect suggests multiple points of entry through which stimulation can elicit cascade processes to spread from longer to shorter timescales-from the surface underfoot [30] and now from the loads at hand.…”
Section: Discussionmentioning
confidence: 65%
“…This network cooperates directly and uninterruptedly with the nervous system and exhibits similar cascade-like structure as found in "neuronal avalanches" [52]. It can be no small coincidence that tensegrity and avalanche models all converge on the same multifractal geometry [53,54] that inspired the development of multiscale PDF quantification of non-Gaussianity [22,24,55]. Hence, this bodywide aspect suggests multiple points of entry through which stimulation can elicit cascade processes to spread from longer to shorter timescales-from the surface underfoot [30] and now from the loads at hand.…”
Section: Discussionmentioning
confidence: 65%
“…In addition to EEG's temporal dependency in AD, MSE analysis also showed lower complexity on a small temporal scale in the frontal region in AD; in comparison, higher complexity was observed across this brain region in AD on a larger temporal scale (Mizuno et al, 2010;Ni et al, 2016). Zorick et al reported that a statistical model based on MF analysis could detect clinical stages of severity and degree of progress from cognitive impairment to AD (Zorick et al, 2020). As described above, MSE and MF analyses have a high ability to detect the complexity in EEG signals of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Zorick et al . reported that a statistical model based on MF analysis could detect clinical stages of severity and degree of progress from cognitive impairment to AD (Zorick et al, 2020 ). As described above, MSE and MF analyses have a high ability to detect the complexity in EEG signals of AD.…”
Section: Introductionmentioning
confidence: 99%
“…This network cooperates directly and uninterruptedly with the nervous system and exhibits similar cascade-like dynamics as in "neuronal avalanches" [46,47]. It is no small coincidence that tensegrity and avalanche models all converge on multiplicativity [48,49] that inspired multiscale quantification of non-Gaussianity [27][28][29]. Hence, MFT approaches suggest multiple points of entry through which stimulation elicits cascades to spread across scalesfrom the surface underfoot [8] to the loads at hand [9] and now from the incoming visual information.…”
Section: Discussionmentioning
confidence: 96%